Pengembangan Sikap Toleransi Siswa Melalui Pembelajaran PKN Di Madrasah Aliyah Negeri 1 Wonosobo - Anisaul Hazhikoh (Politeknik Kampar, 2024)
Character education is education that develops character values in students so that they have values and character as their character, apply these values in their lives, as members of society, and citizens who are religious, nationalist, productive and creative.